Microsatellite characterization and marker development from massive sequencing data of the blenny Salaria pavo - Cardoso, Sara de Jesus Dias, 1988- (2012)
Tese de mestrado. Biologia (Bioinformática e Biologia Computacional). Universidade de Lisboa, Faculdade de Ciências, 2011